FILEMON IN DISKUSSIE: ENKELE HOOGTEPUNTE IN DIE STAND VAN SAKE - Roberts, J. H. (Scriptura, 1987)
Much scholarly attention has recently been paid to Paul’s letter to Philemon. The letter’s briefness allows for experiments in methodology, and current interest in the sociology of early Christianity is attracted by its testimony to social relationships provided by, amongst other, the request of Paul to the Christian slave owner, Philemon, regarding the slave, Onesimus.This review of current research on Philemon takes account of four approaches along the structural line dealing with the letter form, a possible rhetorical form, an experiment with the narrative form, and lastly passes on some results of a discourse analysis.In the section on the letter from the study by Kim on the familiar Greek letter of recommendation with a special section on Philemon, and those by White about the letter body and other related material, was discussed and criticised. The study by Church about Philemon’s rhetorical structure was found to be stimulating. That aspects of rhetorical speech played a vital role in this letter (and other), should be acknowledged. However, to read the letter as a structured oration of the deliberative type, seems to force the issue. The major study by Petersen on the sociology of Paul’s narrative world will long be of consequence. One major drawback was found to be the fact that many exegetical positions which seem to follow from the methodology applied, was in fact based on prior choice, without the benefit to the reader of a close discussion. The results reflected in the last section encompass the delimitation of pericopae and the text cohesion within the various pericopae, as well as a note on the macrostructure of the letter.